Klon Perilaku Menggunakan Jaringan Saraf Tiruan Konvolusional Dalam Game SuperTuxKart - Arrizal Amin; Yuita Arum Sari; Sigit Adinugroho (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
One of the important component of the video game is an artificial intelligence to make the game more competitive. Artificial intelligence used to decide action to reach goal in the game and challenge game player. In the process of developing artificial intelligence, developer needs to program an aritficial intelligence to make a decision for action for each states possible in the game. In this research, artifical neural network will be used as an artificial intelligence inside video game. Neural network will simplify process of developing artificial intelligence because developer does not have to program an algorithm to decide each action for each possible states in the game. Furthermore, neural network can learn or clone gamer's behavior while playing the game. In this research, SuperTuxKart will be used for an example to develop artificial intelligence inside video game. Artificial Intelligence with learning rate 0.0001, momentum 0.3 and epoch 100 reaches accuracy 86.72% for cloning game's behavior while playing video game. So this research concluded that neural network can be used as an artificial intelligence inside game.